From Listening to Learning: Enhancing Vocabulary Through Song “A Little More” by Ed Sheeran - Amelia Suryati; Inayatul Fadilah; Laila Nur Aulia (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Vocabulary mastery is believed to be the very basic aspect in learning EFL, yet it is often difficult to be achieved without appropriate media. The primary objective of this study was to investigate students' perspectives on utilizing Ed Sheeran's “A Little More” as a tool for enhancing vocabulary mastery at Institut Prima Bangsa Cirebon. Employing a qualitative descriptive methodology, the researcher sourced data through direct observation the students do the fill-in-the-blanks and conducting interviews. The results show that using the song can increase students' engagement in learning and motivate them because the atmosphere is fun. The song is also useful in helping the students master the verbs in contextual usage. It further explored how the medium assists learners in enhance their listening and speaking (pronunciation) skills. Thus,